2018
DOI: 10.1021/acschemneuro.8b00259
|View full text |Cite
|
Sign up to set email alerts
|

Ruboxistaurin Reduces Cocaine-Stimulated Increases in Extracellular Dopamine by Modifying Dopamine-Autoreceptor Activity

Abstract: Cocaine is a highly abused drug and cocaine addiction affects millions of individuals worldwide. Cocaine blocks normal uptake function at the dopamine transporter (DAT), thus increasing extracellular dopamine. Currently, no chemical therapies are available to treat cocaine abuse. Previous works showed that the selective inhibitors of protein kinase Cβ (PKCβ), enzastaurin and ruboxistaurin, attenuate dopamine overflow and locomotion stimulated by another psychostimulant drug, amphetamine. We now test if ruboxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Previous studies reported that DRD2-stimulated DAT insertion in striatal synaptosomes requires PKCβ activity ( 39 ). To test whether hM3Dq-stimulated DAT insertion was similarly dependent upon PKCβ activity, we pretreated slices with the PKCβ-specific inhibitor ruboxistaurin ( 46 , 47 ) (50 nM, 30 min, 37 °C), prior to activating hM3Dq with CNO. Ruboxistaurin pretreatment completely abolished CNO-stimulated DAT insertion as compared with vehicle-pretreated slices ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that DRD2-stimulated DAT insertion in striatal synaptosomes requires PKCβ activity ( 39 ). To test whether hM3Dq-stimulated DAT insertion was similarly dependent upon PKCβ activity, we pretreated slices with the PKCβ-specific inhibitor ruboxistaurin ( 46 , 47 ) (50 nM, 30 min, 37 °C), prior to activating hM3Dq with CNO. Ruboxistaurin pretreatment completely abolished CNO-stimulated DAT insertion as compared with vehicle-pretreated slices ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The neurotransmitters that we chose were the catecholamine dopamine, the monoamine serotonin, and the anionic interferants ascorbic acid, and uric acid. Dopamine is an important catecholamine and monoamine neurotransmitter important for understanding the Parkinson's Disease [40], amphetamine abuse [41,42], cocaine abuse [1], and other decision-making capabilities. Serotonin regulates mood and behavior and the depletion of serotonin in the synaptic cleft causes depression [43].…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Neurochemical detection has proven to be important for the understanding and treatment of several diseases, behaviors, and pharmacological drug states. The detection of dopamine is crucial for understanding Parkinson's disease and drug abuse [1], while selective serotonin reuptake inhibitors (SSRIs) are used as treatments for depression [2]. Neurochemical measurements are also important in studying other disease states such as epilepsy [3,4] and obesity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that DRD2-stimulated DAT insertion in striatal synaptosomes requires PKC β activity(40). To test whether hM3Dq-stimulated DAT insertion was similarly dependent upon PKC β activity, we pretreated slices with the PKC β -specific inhibitor ruboxistaurin(47, 48) (50nM, 30 min, 37°C), prior to CNO-stimulated DAT insertion. Ruboxistaurin pretreatment completely abolished CNO-stimulated DAT insertion as compared to vehicle-pretreated slices (Fig.…”
Section: Resultsmentioning
confidence: 99%